Upaya Peningkatan Mutu Proses Dan Hasil Belajar Interaktif Melalui Penilaian Otentik Pada Mata Kuliah Teknologi Pembelajaran Bagi Mahasiswa S1 PGSD FKIP Universitas Bengkulu - Kustianti, Sri Ken (Efektor, 2018)
This study aims to improve the quality of the process and the results of interactive learning through vocational studies Education Technology for undergraduate students PGSD FKIP UNIB. The method of research used class action in collaboration with lecturers model as a researcher. This research was conducted for three cycles. The results showed that learning achievement can effectively improve the quality of the learning process. The study found an innovative model of assessment by conditioned students to build their own potential for self-confidence to appear in the group, openness in accepting criticism, persistence in raising opinions of criticism and attendance as group members. With performance appraisal easier and able to improvise, while students are more proactive in participating.